The Joy Luck Club (Buena Vista Pictures Distribution, 1993)
Produced by Academy Award(R)-winning filmmaker Oliver Stone (Best Picture -- PLATOON) and based on the powerful #1 best-selling book, THE JOY LUCK CLUB tells the uplifting story of four remarkable friends whose extraordinary lives are filled with joy and heartbreak. Their lifelong friendship reveals a mosaic of the startling events and conditions that have shaped their lives -- and how these experiences have affected the hopes and dreams they hold for each of their children. Hailed as one of the must-see films of the year, this exceptional motion picture is sure to entertain and inspire you from beginning to end!